LAYANAN INFORMASI KEPEGAWAIAN BERBASIS CHATBOT WHATSAPP MENGGUNAKAN METODE RULE-BASED DI BKPSDM KABUPATEN BOALEMO - Nunu Fadna Adam; Wahyudin Hasyim; Hilmansyah Gani; Khairul Fathan Habie (LPPM Universitas Muhammadiyah Gorontalo, 2026)
This research aims to design and implement Whatsapp Chatbot-based Personnel Information Services at BKPSDM Boalemo Regency. Several obstacles in personnel information services include dependence on service officers, limited operating hours, and increasing need for information access. The development of the system uses the Waterfall method which includes needs analysis, design, implementation, testing, and maintenance. The chatbot is developed with rule-based techniques and integrated with the WhatsApp API. The results show that chatbots are able to provide real-time automated responses to personnel information, such as leave, promotion, periodic salary increases, mutations, and retirements. Black Box Testing shows that all system functions are running well and as needed. The results of the study show that the implementation of this chatbot increases information accessibility, reduces the workload of officers, and supports the digitization of public services at the Boalemo Regency BKPSDM